Field notes contributed by Randall Pinkston, fall 1992 - Pinkston, Randallet al (1992)
Fall report of birds and locations contributed by Randall Pinkston. Also included are hand drawn sketches and a detailed description of a King Rail sighting. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1992. Plustek - flatbed